Gambaran Indeks Def-t pada Anak Prasekolah di Kelurahan Puhun Pintu Kabun Kecamatan Mandiangin Koto Selayan Kota Bukittinggi - Rosmalia, Dewi; Hidayati, Sri Suci; Zulfikri, Zulfikri (Poltekkes Kemenkes Padang, 2023)
Caries is a dental health disorder that often occurs in early childhood. It causes porous teeth, cavities, and fractures, resulting in less than optimal growth. According to the WHO, caries in children aged 4-5 years in Asia, including Indonesia, reaches 90%. The study aims to determine the description of dental caries based on gender and age group and the distribution of the decidui dental caries index in preschool children. Quantitative research method with descriptive design, research conducted by direct examination, conducted at State Kindergarten 1 Bukittinggi, Raudhatul Athfal Al-Ikhwan, Al-Ikhwan Playgroup, and Kenari Kindergarten. The research sample was all preschool children in Pintu Kabun Village, Mandiangin Koto Selayan District, Bukittinggi City, totaling 113 children. The data were presented in the form of a frequency distribution table. The results showed that the caries of girls was higher than that of boys, based on age group; the higher the age of the child, the greater the number of caries. We found 427 teeth indicating decay, 121 teeth indicating extraction, and only 2 teeth filling, with an average caries of 4.78. The conclusion of the study was that preschool children's dental caries met the bad criteria. It is recommended that children reduce the consumption of sweet and sticky foods, rinse their mouths after eating, brush their teeth twice a day in the morning after breakfast, and at night before going to bed.